Costs matter: The impact of disclosing treatment costs and provider profit on patients' decisions. (March 2017) - Howe, Rebecca; Hassett, Michael J.; Wheelock, Alyse; O'Donoghue, Cristina; Kaplan, Celia; Ozanne, Elissa M.
Highlights: Disclosure of out-of-pocket costs and provider profits resulted in less patient interest in four cancer interventions. Interest decreased for interventions across all health outcomes: early detection, quality of life, local recurrence rates. Patients want to hear about out-of-pocket costs and provider profit during clinical encounters. Abstract: Background: Treatment costs and profits are rarely considered when making treatment decisions despite trends to shift costs directly onto patients. We sought to understand whether out-of-pocket costs and provider profit disclosures impacted patients' care preferences, and how patients preferred to incorporate these issues in their decision making. Methods: We surveyed previous breast cancer patients and unaffected individuals about their preferences for four treatment scenarios (screening with MRI, peg-filgrastim to prevent infection related to chemotherapy, cold cap to reduce hair loss due to chemotherapy, and alternate chemotherapy for adjuvant therapy) that offered varying degrees of clinical benefit. Participants rated their level of interest in each treatment before any disclosure, after disclosure of out-of-pocket costs, and after disclosure of provider profit. Results: Of 216 participants, 33% had a history of cancer. While interest in all treatment options was high initially (68–92% across the four scenarios), it dropped significantly after disclosure of out-of-pocket costs and provider profit. For three scenarios (MRI, peg-filgrastim, cold cap) interest declined to less than 30%. For the chemotherapy drug scenario, where the alternate treatment offered the most clinical benefit, interest was reduced to a lesser extent. Conclusion: Patients expressed significantly less interest in four distinct cancer treatments after disclosure of out-of-pocket costs and provider profit. Discussions about these issues are desired in the clinical encounter. As the economic burden of cancer care shifts to patients, communication about costs and provider profit may be needed to ensure that patients are fully informed when making treatment decisions.